Sex differences in cytokine profiles during suppressive antiretroviral therapy. (15th July 2022) - Vanpouille, Christophe; Wells, Alan; Wilkin, Timothy; Mathad, Jyoti S.; Morris, Sheldon; Margolis, Leonid; Gianella, Sara
Abstract : Objective: Despite lower plasma HIV RNA levels, women progress faster to AIDS than men. The reasons for these differences are not clear but might be a consequence of an elevated inflammatory response in women. Methods: We investigated sex differences in cytokine profiles by measuring the concentrations of 36 cytokines/chemokines by Luminex in blood of women and men (sex at birth) with chronic HIV infection under suppressive therapy. We initially performed a principal component analysis to see if participants clustered by sex, and then fit a partial least squares discriminant analysis (PLS-DA) model where we used cytokines to predict sex at birth. The significance of the difference in nine cytokines with VIP greater than 1 was tested using Wilcoxon test-rank. Further, potential confounding factors were tested by multivariate linear regression models. Results: Overall, we predicted sex at birth in the PLS-DA model with an error rate of approximately 13%. We identified five cytokines, which were significantly higher in women compared with men, namely the pro-inflammatory chemokines CXCL1 (Gro-α), CCL5 (RANTES), CCL3 (MIP-1α), CCL4 (MIP-1β), as well as the T-cell homeostatic factor IL-7. The effect of sex remained significant after adjusting for CD4 +, age, ethnicity, and race for all cytokines, except for CCL3 and race. Conclusion: The observed sex-based differences in cytokines might contribute to higher immune activation in women compared with men despite suppressive therapy. Increased levels of IL-7 in women suggest that homeostatic proliferation may have a differential contribution to HIV reservoir maintenance in female and male individuals. Our study emphasizes the importance of sex-specific studies of viral pathogenesis.